Smoking in the populations health at the Universidad Autónoma de Zacatecas, Mexico - Muñoz Escobedo, José Jesús (2009)
Introduction: there are more than 1.1 billion smokers all over the world, and it has been recognized that tobacco use causes seven deaths every minute. In Mexico, 15 million people are current smokers, and 47 persons die every day because of tobacco use. Few studies have been carried out in Latin America with respect to tobacco use. For instance, in Havana, Cuba, prevalence figures for smokers were 32% for physicians and 46% for nurses. In Mexican health institutions, the prevalence of tobacco use was 28%.Objectives: 1. to determine the prevalence of tobacco use in teachers, students, and workers in the Health Sciences Area within Universidad Autónoma de Zacatecas (UAZ), and 2. To compare prevalence indicators in the aforementioned areas comparing them to the figures found in the Academic Units that make up the health Sciences Area in UAZ.Material and Method: this is a comparative investigation, using direct personal interviews during the 2006-2007 academic term. The different types of responses were quantified. A random sample consisting in approximately 24% or more of each group involved (teachers, students, and administrative personnel).Results: we found that the average prevalence figures for tobacco use in each group were as follows: 20.5% in teachers, 37.75 in students, and 50.25% in administrative personnel. The average prevalence for these groups was 36.12%, which is 8.12% higher compared to prevalence figures found in other Mexican health institutions. An analysis of variance (ANOVA) was performed, confirming that p values were <0.05, and confidence intervals were adequate; consequently, the data obtained has statistical significance.Conclusions: we conclude that the administrative personnel area has the highest prevalence of smokers (50.25% compared to students and teachers figures, 37.75 and 20.5%, respectively), so this is a good reason for performing educational and preventative measures, aiming at promoting tobacco use elimination in the whole Health Sciences area.